Innovative Response Cultural Fashion SMEs Towards Sustainable Business - Dewi Deniaty Sholihah; M. Ilham Naufal; Reiga Ritomiea Ariescy (TIJAB (The International Journal of Applied Business), 2023)
Background: Research aims to identify the critical challenges and marketing strategies faced by cultural fashion SMEs and how they adapt to global changes to sustainable businesses. This research is descriptive qualitative. The data collection technique of this research used the interview method. The selection of informants in this study used a non-probability sampling method with a snowball sampling approach. Objective : This study aims to review the strengths and weaknesses, opportunities and threats based on information obtained from 7 informants Such as crafters, local communities, entrepreneur Udeng Pacul Gowang and representatives of the Sidoarjo Regency Education and Culture Office Method : The strategic factors of Udeng Pacul Gowang obtained are entered in the form of Internal Strategic Factors Analysis Summary (IFAS) and External Factor Analysis Strategic (EFAS) tables, where each factor of the company's strategy is weighted. Giving internal and external weights is based on the calculation of the category value of the assessment of each strategic factor, from here it is seen which one has the greatest influence and the smallest influence to provide an assessment. Next, the researchers matched internal strengths and weaknesses with external opportunities and threats based on the information obtained at the input stage. The analytical tools used in this study are the IE matrix (internal-external), the SWOT Quadrant Matrix, and the SWOT Matrix SWOT Analysis is able to identify the potential and barriers of the cultural fashion industry. Result : Innovative responses by SMEs in the cultural fashion industry are crucial for achieving sustainable business practices. The result of this study found that SMEs can use a range of strategies, including engaging in social and environmental responsibility practices, developing innovative products, and utilizing digital technologies to reach broader markets. Collaboration between SMEs, government, and other stakeholders is also important in developing sustainable business practices. These efforts can lead to positive outcomes, such as improved financial performance, enhanced social and environmental impacts, and increased competitiveness in the global market. Conclusion : (SMEs) play a crucial role in the socioeconomic development of a country. They create job opportunities, empower women, expand rural livelihoods, reduce poverty, contribute to GDP, develop businesses, and enhance entrepreneurial institutions. Among these SMEs are those in the creative industry of cultural fashion, such as Udeng Pacul Gowang products, which have global competitiveness. Udeng Pacul Gowang, made from batik cloth, is a product of state identity that can be used for cultural diplomacy. The development of this business potential requires the support of the government, the private sector, academics, and practitioners. The government can open up opportunities for UKM Udeng Pacul Gowang through policy regulations, while academics and practitioners can collaborate to conduct research and innovation for sustainable business continuity. The younger generation can also practice directly in understanding the business and culture of Udeng Pacul Gowang to regenerate craftsmen. The Sidoarjo Regency government's current support for local culture-based products requires evaluation and follow-up to provide capital grants, soft skills training, and appropriate technology for the digital era's challenges. Keywords: marketing strategy; cultural fashion; smes; sustainable business